UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU IPS DI SMA NEGERI 1 V KOTO KAMPUNG DALAM KECAMATAN V KOTO KAMPUNG DALAM KABUPATEN PADANG PARIAMAN - Mardia, Watna; Kaksim, Kaksim; Elvawati, Elvawati (Pendidikan Sosiologi, 2013)
Research the author here is How to Increase Teachers Professional Competence IPS At SMA Negeri 1 V Koto Kampung Kampung In District In District V Koto Padang Pariaman. This study uses a qualitative approach Descriptive type. Informant selection techniques are Proposive Sampling and data collection methods were observation, interview and documentation with data analysis Milles Huberman. Based on the results of the study authors that the Improving Teacher Professionalism IPS SMA Negeri 1 V Koto Kampung In District V Koto Kampung Padang Pariaman In the district there are 6 efforts made by teachers to improve their professional competence, namely: Discussion, Upgrading, Seminars, Workshops, Continuing kejenjang school Utilizing higher and mass media.